What do premiums paid for bank M&As reflect? The case of the European Union - Jens Hagendorff; Ignacio Hernando; Maria J. Nieto; Larry D. Wall (Federal Reserve Bank of Atlanta, 2010)
We analyze the takeover premiums paid for a sample of European bank mergers between 1997 and 2007. We find that acquiring banks value profitable, high-growth, and low-risk targets. We also find that the strength of bank regulation and supervision and of deposit insurance regimes in Europe has measurable effects on takeover pricing. Stricter bank regulatory regimes and stronger deposit insurance schemes lower the takeover premiums paid by acquiring banks. This result, presumably in anticipation of higher compliance costs, is mainly driven by domestic deals. Also, we find no conclusive evidence that bidders seek to extract benefits from regulators either by paying a premium for deals in less regulated regimes or becoming too big to fail.
Keywords: G21; G34; G28; 330; banks; mergers; premiums; Europe